Mechanically compliant implants as a strategy to decrease foreign body reaction to nerve interfaces - Carnicer-Lombarte, Alejandro; Barone, Damiano G.; Malliaras, George G.; Fawcett, James; Franze, Kristian (Transactions of the Annual Meeting of the Society for Biomaterials and the Annual International Biomaterials Symposium, 2019)
Statement of Purpose: Neural interfaces are unique tools capable of establishing connections between the nervous systems and electronics; offering great potential in both clinic and basic research. Peripheral nerves are particularly attractive sites to position a neural interface, given the ease of access of these structures and the direct correlation between action potential transmission and activity at their target structure. Although many designs for peripheral nerve interfaces have been developed, they all face a major challenge upon chronic implantation: the foreign body reaction (FBR). This response, characterized by inflammation and fibrosis around the implanted body resulting in a build-up of a dense fibrotic capsule, occurs irrespective of the implanted material’s chemical properties. Implantable materials are, however, orders of magnitude stiffer than body tissues, which may tag them as foreign and trigger the foreign body response. In order to avoid this FBR, we have tested low-stiffness materials as potential components for neural interface manufacture. We prepared nerve implants coated with polyacrylamide hydrogels and silicone elastomers with very low mechanical stiffnesses, and evaluated the resulting FBR when chronically implanted in vivo.
CRIS-Team Scopus Importer:2020-08-12